Influence of the Vibration Exposure on Shoulder and Back Extensor Muscles Activity During Forward-head and Over-head Task - Cheon-jun Park; Duk-hyun An; Jae-seop Oh; Won-gyu Yoo (Korean Research Society of Physical Therapy, 2023)
Background: Several factors contribute to shoulder pain, including abnormal neck posture, repeated use of the upper limbs, work involving raising the upper limbs above the head, and the effects of vibration. However, previous study has reported that constant vibration exposure could impact improvement of the stability on joints related with muscle recruitment and activation. For this difference reason, we need to verify for the complex study of relationship with repetitive upper limb movements, poor head posture, and constant vibration exposure. Objects: Our study was made to investigate the influence of vibration exposure on the shoulder muscle activity during forward-head and over-head tasks with isometric shoulder flexion. Methods: In a total of 22 healthy subjects, surface electromyography (EMG) data were collected from shoulder muscles (upper/lower trapezius, serratus anterior, and lumbar erector spinae) on tasks (neutral-head task [NHT], forward-head task [FHT], and over-head task [OHT]) with and without vibration exposure. Results: In all tasks, the EMG data of the upper trapezius and serratus anterior significantly increased with vibration exposure (p < 0.05). Furthermore, the EMG data of the lumbar erector spinae significantly increased with vibration exposure in the NHT and FHT (p < 0.05). Conclusion: We suggest that continuous vibration exposure during the use of hand-held tools in the tasks could be associated with harmful effects in the workplace. Lastly, we clinically need to examine the guidelines regarding the optimal posture and vibration exposure.